3D‐Printed Biomaterials for Guided Tissue Regeneration. Issue 9 (22nd January 2018) - Zhang, Ben; Song, Jie
Abstract: Fabrication of 3D scaffolds with interconnected macro‐/microporosity, compositional gradient, biological cues, and precise geometric configurations matching with that of a tissue defect, along with the choice of appropriate biomaterials, is central to the success of scaffold‐guided tissue‐regeneration strategies. Customized high‐speed 3D‐printing technology enables efficient fabrication of 3D scaffolds for regenerative‐medicine applications. In addition to recent technological advances in 3D‐printing methods and instrumentation, progress has been made in the expansion of printable biomaterials and cell‐laden bioinks. Here, a brief overview of the 3D‐printing techniques most commonly used for biomedical applications is given, followed by a discussion of common bioceramics, natural biopolymers, and synthetic degradable thermoplastic polymers, as well as their cell/biofactor‐laden composites used for 3D printing. Advantages and limitations of these printing techniques and bioinks for various tissue repair/regeneration applications are highlighted. Abstract : 3D‐printing technology provides an efficient and customized strategy to fabricate 3D biomaterial scaffolds with controlled porosity and precise architecture for scaffold‐guided tissue regeneration. A brief overview of common 3D‐printing techniques for tissue engineering is followed by the discussion of bioceramics, cell‐laden bioinks, functional thermoplastic polymers, and their complex composites 3D printed for skeletal and soft tissue regeneration.